Development of a modified Green–Ampt model considering the unsaturated zone - Li, Yuchen; Nie, Weibo; Feng, Zhengjiang; Li, Ge (Biosystems engineering, 2025)
The Green–Ampt (GA) model is widely used for estimating water infiltration in soil. However, the assumptions of a rectangular saturated piston flow model limit its capacity to accurately represent the actual infiltration process. This study developed a modified Green–Ampt (MGA) model that considers the unsaturated zone during infiltration. This model assumes an elliptical distribution for the soil water content in the unsaturated zone and the average unsaturated hydraulic conductivity is equal to that corresponding to the average soil water content. It also offers a reasonable correction term for the average suction head at the wetting front. Results indicate a nonlinear decrease in the thickness ratio of the unsaturated zone to the wetting front. Validation of the MGA model was conducted using laboratory experiments and one-dimensional vertical infiltration simulation for 12 USDA soil textural classes by HYDRUS-1D. Mean absolute error (MAE), mean relative error (MRE), and percentage bias (PB) values were calculated to evaluate model performance. The average MAE, MRE and PB values between the estimated wetting front by MGA model with the measured and simulated values by HYDRUS-1D are 8.8 mm, 6.6 %, −2.7 %, and 20.6 mm, 6.4 %, −4.3 %, respectively. And the average MAE, MRE and PB values for the cumulative infiltration are 2.7 mm, 5.9 %, −3.9 %, and 2.1 mm, 4.0 %, −1.6 %, respectively. The estimated errors of the MGA model were lower than those of the GA model, indicating that the MGA model provides accurate estimates for one-dimensional vertical infiltration and is suitable for a variety of soil textures. •A modified Green–Ampt (MGA) model considering the unsaturated zones is developed.•The MGA model can accurately estimate one-dimensional vertical infiltration process.•The MGA model is validated by comparing measured and simulation values by HYDRUS-1D.•The ratio of unsaturated zone to wetting front exhibits a nonlinear decreasing trend.